Evaluation of Polyethylene-Based Long Lasting Treated Bed Net Netprotect on Anopheles Mosquitoes, Malaria Incidence, and Net Longivity in Western Kenya - M. T. O. Odhiambo; O. Skovmand; J. M. Vulule; E. D. Kokwaro (Journal of Tropical Medicine)
We studied the effect on malaria incidence, mosquito abundance, net efficacy, net use rate, chemical analysis, and holes of a long lasting insecticide treated bed net (Netprotect) in western Kenya, 2007–2010. Nets were hung in 150 households 6 months before they were hung in a second, 2 km away. Indoor resting densities were monitored by pyrethrum spray catch and malaria cases by passive detection using clinical manifestations and rapid diagnostic test. The probability of finding An. arabiensis in the control area was 2.6 times higher than that in intervention area during the first 6 months. Human blood feeding index of Anopheles funestus declined 17%. After bed nets were hung in the second area, malaria incidence declined 25% down to the level in the first area. Incidence remained at this low level for 2 years. 90% of collected nets were efficacious after 3-year use. Deltamethrin dosage declined from 1.9 to 0.5 g/kg over 3 years. Attrition rate after 3 years was 21%. WHO hole index changed from 333 to 114 to 381 over the three years. This index summarizes the numbers of holes in size categories and multiplies with the mean hole area per category. It is very sensitive to the impact of big holes in a few nets.